2017
DOI: 10.18632/oncotarget.19513
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of targeting PFKFB3 as a therapeutic strategy against cancer

Abstract: 6-phosphofructo-2-kinase/fructose-2, 6-bisphosphatases (PFKFBs) are bifunctional enzymes which regulate the transformation between fructose-2, 6-bisphosphate (F2, 6BP) and fructose-6-phosphate (F6P) in the process of glucose metabolism. Among the four isozymes (PFKFB1-4), PFKFB3 has stronger kinase activity than phosphatase activity, resulting in the synthesis of F2, 6BP and the promotion of glycolysis. Additionally, PFKFB3 plays a key role in cell cycle regulation. It has been confirmed that PFKFB3 is upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 51 publications
5
56
0
Order By: Relevance
“…PFKFB3 is a potent regulator of glycolysis and is frequently upregulated in cancers [ 167 ]. Various inhibitors of PFKFB3 have been reported, including the weak PFKFB3 inhibitor, 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO).…”
Section: Therapeutic Opportunities Targeting Altered Ccmmentioning
confidence: 99%
“…PFKFB3 is a potent regulator of glycolysis and is frequently upregulated in cancers [ 167 ]. Various inhibitors of PFKFB3 have been reported, including the weak PFKFB3 inhibitor, 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one (3PO).…”
Section: Therapeutic Opportunities Targeting Altered Ccmmentioning
confidence: 99%
“…In hypoxia, in the absence of HIF1a, we found a blockage at the metabolic step mediated by fructose-bisphosphate aldolase (Aldolase A, ALDOA), catabolizing the cleavage of Fru-1,6BP to glyceraldehyde 3-phosphate and dihydroxyacetone phosphate. Previously, it has been shown that PFKB3 was key in regulating glycolysis one step earlier, and has been the focus of several approaches to develop inhibitors (31).…”
Section: Discussionmentioning
confidence: 99%
“…PFKFB3 inhibitors reduce anaerobic glycolysis by blocking the 6-Phosphofructo-2-kinase/fructose-2,6-bisphosphatase 3 enzyme. This protein is highly expressed by tumour cells, explaining the interest of PFKB3 inhibitors for cancer therapy ( Lu et al, 2017 ), but also in endothelial cells. Indeed, inhibition of PFKB3 reduces endothelial cell proliferation and angiogenesis ( Cantelmo et al, 2016 ; Schoors et al, 2014 ), but plays also an anti-inflammatory effect by limiting NLRP3 activation ( Finucane et al, 2019 ).…”
Section: Concluding Remarks: Therapeutic Opportunitiesmentioning
confidence: 99%